Introduction. Issue 2 (23rd February 2016) - Petersson, Magnus; Slensvik, Thomas; Ydstebø, Palle
ABSTRACT: This special issue contains articles contributing to the understanding of the role military doctrine plays in strategic theory and practice. The authors scrutinize the function and development of doctrine, the use of force and the role of doctrine, alliances and doctrine, and small states and doctrine. The contributions are related to the wider scholarly and practical context of how doctrine is developed and implemented. The authors use functional, cultural and institutional explanations in their articles. They also give practical recommendations regarding how to increase the effectiveness of the doctrine development process, and the effectiveness of doctrine itself in relation to the use of force.